From the mirror to the mask : techniques of self-representation in Charles Baudelaire, Odilon Redon and James Ensor - Moran, Claire Noelle (Trinity College (Dublin, Ireland). Department of French, 2004)
This thesis considers the question of self-representation in the art and literature of nineteenth-century France and Belgium. The evolution from the mirror to the mask as a means of representing self is discussed through three case studies, focusing on the work of Charles Baudelaire, Odilon Redon and James Ensor. The mirror, as referred to in this study, serves as an analogy for mimesis and representationalism, while the mask refers to non-representational art. Three ideas are at the core of the discussion: the crisis of the self, the advent of modernity and the role of caricature. The approach is interdisciplinary, drawing upon art and literary criticism, as well as on critical theory and psychoanalysis.
Keywords: French, Ph.D.; Ph.D. Trinity College Dublin